Enabling Cost-Benefit Analysis of Data Sync Protocols - Boskov, Novak; Trachtenberg, Ari; Starobinski, David (Computer (Long Beach, Calif.), 2023)
We describe a new middleware called GenSync that abstracts the subtleties of the state-of-the-art data synchronization protocols, allows users to choose protocols based on a comparative evaluation under realistic system conditions, and seamlessly integrates protocols in existing applications through a public application programming interface.